2018
DOI: 10.1021/acsami.8b03322
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Low-Temperature Processed Thin-Film Transistors Based on Indium Oxide/Zinc Oxide Heterostructures

Abstract: The influence of the composition within multilayered heterostructure oxide semiconductors has a critical impact on the performance of thin-film transistor (TFT) devices. The heterostructures, comprising alternating polycrystalline indium oxide and zinc oxide layers, are fabricated by a facile atomic layer deposition (ALD) process, enabling the tuning of its electrical properties by precisely controlling the thickness of the individual layers. This subsequently results in enhanced TFT performance for the optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 62 publications
4
51
1
Order By: Relevance
“…Although the surface roughness does not change during the deposition and patterning of the bottom ITZO layer, the wet etch and photolithography processes can produce defects or impurities which cause higher SS value. In addition, Krausmann et al reported the effect of channel layer thickness on the generation of bulk defects . In our results, regardless of the material, the TFT devices with thick active layer exhibits a higher SS value than those with thin active layer.…”
Section: Electrical Properties Of the Indicated Mo Tfts (The Values Asupporting
confidence: 65%
“…Although the surface roughness does not change during the deposition and patterning of the bottom ITZO layer, the wet etch and photolithography processes can produce defects or impurities which cause higher SS value. In addition, Krausmann et al reported the effect of channel layer thickness on the generation of bulk defects . In our results, regardless of the material, the TFT devices with thick active layer exhibits a higher SS value than those with thin active layer.…”
Section: Electrical Properties Of the Indicated Mo Tfts (The Values Asupporting
confidence: 65%
“…The measured growth rates of the individual metal oxides were found to be smaller than the ones calculated by the rule of mixture. This phenomenon is well documented and originates from a retarded adsorption of the precursors on the substrate [33] due to a changing surface chemistry during the deposition process [3] . To assess the homogeneity and the morphology of the deposited thin layers, high resolution transmission electron microscopy (HRTEM) was performed on a focused ion beam (FIB) prepared cross‐section of the deposited thin‐film (see Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…where V G , V T , and V P are the gate, threshold, and percolation voltages and K is a pre‐factor, the exponent γ is obtained, which provides information about the predominant transport mechanism [50] . Values for γ around 0.1 indicate a trap‐limited conduction (TLC), whereas values around 0.7 indicate a percolation conduction (PC) [3,50] . The dependency of the field‐effect mobility on the gate‐voltage for the discussed transistors is shown in Figure 7, while the respective values are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, disordered structural network and high density of intrinsic defects in the AOS materials largely affect electrical performances (e.g., electron mobility and stability) of the TFTs and limit their industrial applications in next‐generation electronic device platforms. To overcome these limitations, a notable strategy, i.e., stacked‐layer channel combining different individual oxide semiconducting materials, has been proposed in recent years and successfully implemented to enhance the device performances . Park and Lee reported a bilayer IZO/IGZO TFT with the field‐effect mobility (μ FE ) of 47.7 cm 2 V −1 s −1 and threshold voltage ( V TH ) of 1.57 V, where the mobility enhancement (i.e., ≈2.3 times higher than that of a single‐layer IGZO TFT) was induced by a high electron density of the IGZO layer with electrons injected from the IZO layer of the stacked structure .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al successfully fabricated the high‐performance oxide TFTs composed of the IZO (or InSnO) and IGZO active layers, showing μ FE of 51.3 cm 2 V −1 s −1 (104 cm 2 V −1 s −1 ), but the insight physics remained unexplored . The superior performance parameters of the stacked‐layer TFTs in refs were attributed to the formation of 2D electron gas (2DEG) at the heterointerface between the respective metal oxide film, where the 2DEG‐like system formed in the TFTs requires careful tuning of the quantized energy level in the semiconducting layers (e.g., In 2 O 3 /ZnO and In 2 O 3 /Al 2 O 3 ) as well as the suitable device architectures to enable a band‐like electron transport …”
Section: Introductionmentioning
confidence: 99%